An engineered Japanese encephalitis virus mRNA-lipid nanoparticle immunization induces protective immunity in mice - Zhu, Jiayang; He, Caiying; Liu, Yusha; Chen, Min; Zhang, Jiayi; Chen, Dong; Ni, Hongxia; Wen, Jinsheng (Frontiers in Microbiology, 2024)
IntroductionJapanese encephalitis virus (JEV) and Zika virus (ZIKV) pose a severe threat to human health. Our previous research results, as well as those of other research groups, indicated that antibodies (Abs) induced by JEV infection or JEV vaccine vaccination could enhance ZIKV infection in vitro and exacerbate the mortality of ZIKV-infected mice, vice versa, which is known as antibody-dependent enhancement (ADE). Although studies on other flaviviruses revealed that altering the amino acid residues located in the fusion loop (FL) of envelope (E) protein can reduce the level of flavivirus-cross-reactive Abs, thereby abating the ADE of heterologous flavivirus infection, it is unclear whether this strategy is equally applicable to JEV.MethodsIn this study, we constructed recombinant adenoviruses and nucleotide-modified mRNA-lipid nanoparticle (LNP) encoding JEV wild-type E protein or E protein mutant (designated as Ad5-JEV-EWT and Ad5-JEV-Emut; JEV-EWT mRNA-LNP, and JEV-Emut mRNA-LNP). We evaluated the immunogenicity of these vaccine candidates in mice and the capacity of vaccine-immune mouse sera to neutralize JEV infection or mediate ADE of ZIKV infection in vitro and in vivo.ResultsAd5-JEV-Emut or JEV-Emut mRNA-LNP immunization induced ZIKV-cross-reactive Ab response which is dramatically lower than that induced by Ad5-JEV-EWT and JEV-EWT mRNA-LNP, respectively. The levels of JEV-neutralizing Abs induced by Ad5-JEV-Emut or JEV-Emut mRNA-LNP are comparable to that induced by Ad5-JEV-EWT and JEV-EWT mRNA-LNP, respectively. The ability of Abs induced by Ad5-JEV-Emut to enhance ZIKV infection in vitro is attenuated as compared with that induced by Ad5-JEV-EWT. Moreover, JEV-Emut mRNA-LNP immunization elicited potent T cell response similar to JEV-EWT mRNA-LNP in mice. Mice immunized with each mRNA-LNP exhibited lower level of serum viral load than the mock-immunized mice post JEV challenge. Mice receiving JEV-EWT mRNA-LNP-immune mouse sera exhibited ADE post ZIKV challenge whereas passively transferred JEV-Emut mRNA-LNP-immune mouse sera did not lead to obvious ADE of ZIKV infection in recipient mice. Most importantly, maternally acquired Abs did not enhance the mortality of 1-day-old neonates born to JEV-Emut mRNA-LNP-immunized mice post ZIKV challenge.DiscussionThese results suggest that optimizing the FL sequence of JEV could significantly reduce the level of JEV/ZIKV-cross-reactive Abs and abrogate the ADE of ZIKV infection, providing a promising strategy to develop effective and safety JEV vaccine.